PENGARUH CEO DUALITY DALAM HUBUNGAN ORGANIZATIONAL SLACK DAN ESG TERHADAP KINERJA PERUSAHAAN - Tandiamal, Fritzline Geralda; Daromes, Fransiskus Eduardus; Tangke, Paulus; Daromes, Fransiskus E. (Jurnal Akuntansi, 2025)
This study examines the effect of organizational slack and Environmental, Social, and Governance (ESG) on firm performance. It compares these relationships between companies with CEO duality and those with CEO non-duality. The study is grounded in the resource-based view (RBV) and stakeholder theory. The population of this research consists of non-financial companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The data used are financial statements and annual reports, with a total of 145 company samples selected using the purposive sampling method. The results indicate that organizational slack has a positive and significant effect on firm performance. ESG also has a positive and significant effect on firm performance. In addition, CEO duality strengthens the effect of both organizational slack and ESG on firm performance. This research provides theoretical contributions by reinforcing the RBV and stakeholder theory, as well as practical implications for management and investors in leveraging slack, integrating ESG practices, and considering leadership structure as a factor that can improve firm performance.